Combined antiproliferative activity of imatinib mesylate (STI-571) with radiation or cisplatin in vitro - Yerushalmi, R.; Nordenberg, J.; Beery, E.; Uziel, O.; Lahav, M.; Luria, D.; Fenig, E. (Experimental Oncology, 2007)
Little is known about the interaction of novel anticancer drugs with other treatment modalities. The aim of this study was to examine the effect of combining imatinib mesylate (STI-571) with radiation or cisplatin on the survival of two human solid tumor cell lines – SKNMC cells derived from Ewing sarcoma and breast cancer MCF-7 cells. Methods: Cell proliferation was determined using the sulphorodamine B cytotoxicity assay. Cell cycle analysis was performed with flow cytometry. Apoptosis was determined using a commercial cell death ELISA plus kit. Phosphorylated AKT, which has been suggested to be involved in radiation resistance, was detected by Western blot analysis. Results: Exposure of SKNMC cells to STI-571 resulted in a dose-dependent antiproliferative effect and a decrease in phosphorylated AKT expression. There was no evidence of apoptosis. The combination of STI-571 with radiation or cisplatin had an additive antiproliferative effect in SKNMC cells (60% reduction in cell number). A similar effect was observed in human MCF-7 breast cancer cells. Conclusion: STI-571 improves the outcome of cisplatin or irradiation treatment in vitro. AKT pathway may play a role in the additive effect of STI-571 and irradiation.